Exploring the Reactivity of 4-Hydroxydithiocoumarin to Access Novel Organosulfur Compounds and Some of Their Anticancer Activity Study - Ali, Ahmed (My University, 2026)
The title of the thesis is “Exploring the Reactivity of 4-Hydroxydithiocoumarin to Access Novel Organosulfur Compounds and Some of Their Anticancer Activity Study”. The whole thesis work is organized into six chapters.
Khan, Abu Taleb